SIMPLE EXPRESSION FOR THE LINEAR STARK BROADENING CONSTANT OF HYDROGEN LINES - Bayazitov, U. Sh. (Одеські астрономічні публікації, 2017)
A simple analytic expression is presented allowing to take into account the Stark broadening constant of hydrogen lines.